Molecular Dynamics Simulation of New Tetraethylammonium-Based Amino Acid Ionic Liquids - Haron, Naimah (2011)
Ionic liquids (ILs) or molten salts with melting temperature below 100 °C are highly desirable due to their unique physical and chemical properties which gave them extensive applications ranging from biomedicine, chemical and nuclear industries. Molecular dynamics (MD) simulation can be used to predict new molecular structures such as ILs and proteins. In addition, some properties can be predicted by using MD simulation such as density, viscosity and also self-diffusion coefficient. Therefore, MD simulations for three types of amino acid ionic liquids (AAILs), i.e. tetraethylammonium L-glutaminate [N2222][L-Gln], tetraethylammonium Lisoleucinate [N2222][L-Ile] and tetraethylammonium L-lysinate [N2222][L-Lys] have been performed in order to investigate their physical properties. A detailed analysis of the structure and cation-anion interaction in above mentioned AAILs was also provided by Density Functional Theory (DFT) method at B3LYP/6-31G//6-31++G** level. It was shown that the viscosity values of all AAILs derived from molecular dynamics simulations are consistent with the experimental data available. It was also found that the viscosity of AAILs with branched side chain on the amino acid anion such as [N2222][L-Ile] was higher compared to a straight alkyl chain like [N2222][LLys]. In the case of [N2222][L-Gln], the presence of hydrogen bonding donor or acceptor at the side chain of the amino acid anion has increased the viscosity through intermolecular hydrogen bonds between the amino proton and carbonyl oxygen atom. This suggests that the most prominent factor that contributes to the viscosity of AAILs was anions structure. The densities of AAILs from the simulation results were also consistent with experimental. The self-diffusion coefficients, (D) for these three AAILs showed that D[N2222][L-Lys] > D[N2222][L-Ile] > D[N2222][L-Gln] due to its viscosity from lowest to highest. Additionally, the same trend has also been reported by other researchers for Mean Square Displacement (MSD) and D for different ionic liquids. Based on Radial Distribution Function (RDF) results, there were one shoulder peak at 6.00 Å for [N2222][L-Lys] in cation-anion area, which might be due to the tendency of anions distributed from the spherical cation centre. Besides that, this study has shown that each cation was surrounded by seven anions for [N2222][L-Gln] and [N2222][L-Ile] and eight anions for [N2222][L-Lys] according to Spatial Distribution Function (SDF) results. The clear picture of the microstructure details of the important AAILs, which has not yet been systematically investigated in the experimental and theoretical fields can be performed using DFT calculations combined with molecular dynamic simulations. The theoretical results can offer valuable information for the further designing of tetraethylammonium-based ILs.